1980
DOI: 10.1128/iai.27.1.97-101.1980
|View full text |Cite
|
Sign up to set email alerts
|

Binding of cholesterol by sulfhydryl-activated cytolysins

Abstract: The binding of cholesterol by pneumolysin, alveolysin, and streptolysin 0 has been demonstrated. The properties of the cytolysin-cholesterol interaction parallel those of cytolysin-erythrocyte interaction in that the reaction is rapid, temperature independent, decreased at elevated pH, and shows the same specificity with respect to other related sterols. However, oxidized or p-hydroxymercuribenzoate-treated toxin showed no decrease in cholesterol-binding activity, whereas the ability of cytolysin to bind to er… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
41
0

Year Published

1988
1988
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 86 publications
(41 citation statements)
references
References 17 publications
(12 reference statements)
0
41
0
Order By: Relevance
“…Because of increasing antibiotic resistance among pneumococci and the suboptimal efficacy of polysaccharide vaccine, the interest has shifted towards pneumococcal proteins. Many proteins, such as autolysin (Garcia et al, 1986;Lock et al, 1992), neuraminidase (Berry et al, 1988;Lock et al, 1988), pneumococcal surface adhesin A (PsaA; Sampson et al, 1994), IgA1 protease (Male, 1979;Poulsen et al, 1996), peptide permeases , pneumolysin (Johnson et al, 1980;Paton, 1996) and pneumococcal surface protein A (PspA; Briles et al, 1988; have been identified and characterized. Among these, pneumolysin and PspA have been studied in detail.…”
Section: Introductionmentioning
confidence: 99%
“…Because of increasing antibiotic resistance among pneumococci and the suboptimal efficacy of polysaccharide vaccine, the interest has shifted towards pneumococcal proteins. Many proteins, such as autolysin (Garcia et al, 1986;Lock et al, 1992), neuraminidase (Berry et al, 1988;Lock et al, 1988), pneumococcal surface adhesin A (PsaA; Sampson et al, 1994), IgA1 protease (Male, 1979;Poulsen et al, 1996), peptide permeases , pneumolysin (Johnson et al, 1980;Paton, 1996) and pneumococcal surface protein A (PspA; Briles et al, 1988; have been identified and characterized. Among these, pneumolysin and PspA have been studied in detail.…”
Section: Introductionmentioning
confidence: 99%
“…The property all thiol-activated toxins have in common is that preincubation with low amounts of cholesterol inhibits haemolytic activity as well as cytolysis of eukaryotic cells. Thus, it is has been suggested that cholesterol is the primary receptor on host cell membranes (Duncan and Schlegel, 1975;Prigent and Alouf, 1976;Jonson et al, 1980). According to this line, inhibition of cytolysis was assumed to be due to occupancy of the cholesterol binding site by free cholesterol.…”
Section: Introductionmentioning
confidence: 99%
“…Cholesterol plays an important role in determining the physical properties and functions of animal cell membranes. In addition to having a modulating effect on membrane fluidity and permeability [Demel et al, 19721, there is evidence that cholesterol may interact directly with certain membrane proteins [Johnson et al, 1980;Asano and Asano, 19881 and possibly regulate their functional activity [McMurchie, 1988;Asano and Asano, 19881. Cholesterol is a n important dietary lipid and has been shown to modulate resistance of mice to infections by some bacteria and viruses, including Listeria monocytogenes [Kos et al, 1979;Kos et al, 19841 and Coxsackie B virus [Campbell et al, 19821 and also MHV-3 [Pereira et al, 19871. MHV-3 is strongly hepatotropic in Balb/c mice but causes only a mild liver infection in A/J mice.…”
Section: Introductionmentioning
confidence: 99%